PENGARUH PENERAPAN LKS BERORIENTASI PENDEKATAN KONSTRUKTIVISTIK TERHADAP HASIL BELAJAR FISIKA SISWA KELAS XI SMA NEGERI 4 PADANG - Silvia Ramadani (Universitas Negeri Padang, 2014)
The article based on research that title “Influence of using student worksheet oriented to constructivistic approach to the ability of the students in grade XI of senior high school 4 Padang”. This research based of demand curriculum to teaching and learning process is maximizing the students involment in the clasroom. The students can build their own knowledge not only by getting the final result from the teacher but also by doing another approaches. One of approaches is constructivistic. By those reasons, that is why this research was conducted to observe the influence of using student worksheet oriented to constructivistic approach to the ability of the students in grade XI of senior high school 4 Padang. Quasi-exsperiment research was developed which randomized control group only design. The population of the research was grade XI IPA in senior high school 4 Padang and sample was selected by applying purposive sampling technique. The data of this research were the final result test of study in cognitive, affective and psikomotor aspect. The instrument of the research were written test to asses cognitive aspect, observation test to asses affective aspect and check list to asses the psychomotor aspect. The data analysis for these three aspect was done by equality test of two averages which use t test that meant that the applying of student worksheet oriented to the constructivistic approach to the students final test of the study in physics in senior high school 4 Padang was about 0,05 in real standard.